Mechanistic insights into endosomal escape by sodium oleate-modified liposomes - Ebrahim Sadaqa; Satrialdi; Fransiska Kurniawan; Diky Mudhakir (Beilstein Journal of Nanotechnology)
Endosomal entrapment significantly limits the efficacy of drug delivery systems. This study investigates sodium oleate-modified liposomes (SO-Lipo) as an innovative strategy to enhance endosomal escape and improve cytosolic delivery in 4T1 triple-negative breast cancer cells. We aimed to elucidate the mechanistic role of sodium oleate in promoting endosomal escape and compared the performance of SO-Lipo with unmodified liposomes (Unmodified-Lipo) and Aurein 1.2-modified liposomes (AUR-Lipo). Liposomes were prepared using the thin-film hydration method, resulting in Unmodified-Lipo, SO-Lipo, and AUR-Lipo formulations. The particle sizes were 102.2 ± 3.30 nm for Unmodified-Lipo, 109.6 ± 7.65 nm for SO-Lipo, and 151.9 ± 5.88 nm for AUR-Lipo, with polydispersity indices below 0.25, indicating uniform size distribution. Endosomal escape efficiency was evaluated through confocal microscopy by measuring the colocalization of labeled liposomes with lysosomal markers, quantified using Pearson’s correlation coefficient. Lipid mixing assays assessed the potential fusogenic effect, and molecular dynamics (MD) simulations explored the interactions of protonated sodium oleate (SO) with the endosomal membrane. Results demonstrated that SO-Lipo exhibited superior endosomal escape compared to Unmodified-Lipo, as evidenced by reduced colocalization with lysosomal markers, and achieved comparable efficacy to AUR-Lipo with lower cytotoxicity. Lipid mixing assays confirmed the potential fusogenic effect of SO with endosomal membrane models. MD simulations revealed that under acidic endosomal conditions, SO is protonated to oleic acid, which integrates into the membrane, enhancing fluidity and promoting fusion events essential for cytosolic release. SO-Lipo enhance endosomal escape through a fusogenic mechanism, facilitating cytosolic delivery with reduced cytotoxicity. This approach offers a safer and more effective option for targeted drug delivery applications.